DEVELOPMENT STRATEGY FOR CAPTURE FISHERIES BASED ON BLUE ECONOMY IN TANJUNG JABUNG BARAT DISTRICT, JAMBI, INDONESIA: STRATEGI PENGEMBANGAN PERIKANAN TANGKAP BERBASIS BLUE ECONOMY DI KABUPATEN TANJUNG JABUNG BARAT, JAMBI, INDONESIA - Farhan Ramdhani; Muhammad Hariski; Yoppie Wulanda; Sri Novianti; Wulandari Wulandari; Izza Mahdiana Apriliani; Anta Maulana Nasution (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
Tanjung Jabung Barat Regency, Jambi Province, has considerable potential for marine capture fisheries; however, fisheries development still faces several sustainability challenges, including the dominance of traditional fishing technology, limited infrastructure, weak market access, low post-harvest quality control, and increasing pressure on fish resources. These conditions indicate the need for a fisheries development strategy aligned with the Blue Economy concept, which emphasizes economic growth while maintaining the sustainability of marine ecosystems and improving coastal community welfare. This study aims to formulate a data-based capture fisheries development strategy in West Tanjung Jabung Barat Regency using SWOT, TOWS, and QSPM approaches. The research was conducted from April 2024 to February 2025 in the Kuala Tungkal Fisheries Center, West Tanjung Jabung Regency. The results indicate that the major strengths include the potential of the fish resource and government support, while the main weaknesses are the dominance of traditional fishing gear and limited fisheries infrastructure. Significant opportunities include strong domestic and international market demand, whereas threats include destructive fishing practices and global market competition. Twelve alternative strategies were identified. The priority strategy is strengthening fisheries market integration through improved product quality, marketing networks, and institutional support. In addition, fisheries infrastructure improvement and environmentally friendly fishing technology adoption are essential to support Blue Economy-based fisheries management. These strategies are expected to enhance fisheries productivity, improve coastal community welfare, and maintain sustainable fishery resources in West Tanjung Jabung Barat Regency.